2016
DOI: 10.1002/chem.201601918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Interactions on Electron‐Transfer and Antioxidant Activity of Bis(alkanol)selenides: A Radiation Chemical Study

Abstract: Understanding electron-transfer processes is crucial for developing organoselenium compounds as antioxidants and anti-inflammatory agents. To find new redox-active selenium antioxidants, we have investigated one-electron-transfer reactions between hydroxyl ((.) OH) radical and three bis(alkanol)selenides (SeROH) of varying alkyl chain length, using nanosecond pulse radiolysis. (.) OH radical reacts with SeROH to form radical adduct, which is converted primarily into a dimer radical cation (>Se∴Se<)(+) and α-{b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…GPx activity of the DSePA–gelatin conjugate was determined by NADPH–GSH–GSSG coupled assay. 38 Briefly, 30 μg ml −1 of selenium equivalent of DSePA or DSePA–gelatin conjugate was mixed with assay buffer (0.1 M Tris, pH 7.4) containing 2.1 mM GSH, 250 μM NADPH and 0.5 units per ml of GR. The reaction was initiated by adding 300 μM of cumene hydroperoxide and monitored by following a decrease in absorbance of NADPH at 340 nm as a function of time.…”
Section: Methodsmentioning
confidence: 99%
“…GPx activity of the DSePA–gelatin conjugate was determined by NADPH–GSH–GSSG coupled assay. 38 Briefly, 30 μg ml −1 of selenium equivalent of DSePA or DSePA–gelatin conjugate was mixed with assay buffer (0.1 M Tris, pH 7.4) containing 2.1 mM GSH, 250 μM NADPH and 0.5 units per ml of GR. The reaction was initiated by adding 300 μM of cumene hydroperoxide and monitored by following a decrease in absorbance of NADPH at 340 nm as a function of time.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 It is considered that the physicochemical properties of selenium are quite similar to sulfur; nevertheless, their radical-mediated redox chemistry differs significantly. 1,[9][10][11][12] Radiation chemical studies on certain water-soluble aliphatic selenium compounds from one of the authors' group have shown that selenium-centered radicals exhibit extra stability and lower reactivity than analogous sulfur-centered radicals. [12][13][14][15][16] Previous antioxidant studies on selenium-bearing carboxylic acids have shown that they have higher activity, but the underlying reaction mechanism and product distribution vary considerably depending on the chain length.…”
Section: Introductionmentioning
confidence: 99%
“…1,[9][10][11][12] Radiation chemical studies on certain water-soluble aliphatic selenium compounds from one of the authors' group have shown that selenium-centered radicals exhibit extra stability and lower reactivity than analogous sulfur-centered radicals. [12][13][14][15][16] Previous antioxidant studies on selenium-bearing carboxylic acids have shown that they have higher activity, but the underlying reaction mechanism and product distribution vary considerably depending on the chain length. 13,14 Furthermore, it is worth noting that the carboxylic group, found in various naturally occurring antioxidants such as lipoic acid, plays a significant role in their activity.…”
Section: Introductionmentioning
confidence: 99%
“…For GNP-Selenium studies, we have employed bis-2-ethanolselenide (EOH-Se-EOH) as a model SE compound and for MNP-Selenium studies we used various Se containing aminoacid derivatives such as selenoglycine derivative (SeG) and selenoserine derivative (SeS). Synthesis of selenium compounds are reported in our earlier papers [10,11]. The chemical structure of selenium compound used for GNP interaction is given in scheme 1.…”
Section: Introductionmentioning
confidence: 99%